The Early Warning System Effectiveness of the Maritime Security Agency of the Republic of Indonesia (Bakamla RI) in the Prevention of Drug Invention through the Sea Lane - Yosy Gustasya; Raymundus Putra Situmorang; Regil Kentaurus Harryes (The Republic of Indonesia Defense University, 2023)
The Republic of Indonesia Maritime Security Agency (Bakamla RI) was formed based on the mandate of Article 59 Paragraph 3 of Law Number 32 of 2014 concerning Maritime Affairs. Bakamla RI has implemented an early warning system to ensure security and safety in Indonesian waters and jurisdiction. The Bakamla RI Early Warning System (EWS), known as a choke point for maritime security and safety, has already been built and spread throughout Indonesian waters. However, in reality, drug smuggling by sea is still common. Drug smuggling by sea is still dominant today. The United Nations Office on Drugs and Crime (UNODC) revealed that 80% of drug trafficking is carried out by sea. Narcotics transactions in the middle of the sea are very safe transactions, this is due to very weak supervision in the middle of the sea by officers. The purpose of this study is to analyze the mechanism and effectiveness of an early-stage warning system in preventing drug smuggling by sea. This study uses a qualitative descriptive method with interview data collection techniques. Research shows that the Early Warning System Series produces ship detection and assistance data that can be processed into ship anomaly information. The application of the Bakamla RI early warning system to prevent drug smuggling by sea has not been effective. The difficulty of realizing information between agencies and the weak synergy in exchanging information are the main obstacles to the efficiency of the early warning system. Therefore, it is recommended to increase the capability of the Bakamla RI Early Warning System by integrating the Command and Control Center (Puskodal) or Control Center (Pusdal) of related agencies, as well as equipping it with monitoring equipment that integrates the Early Warning System.